PENERAPAN APLIKASI AT-TASHIL PADA MATERI AL-MAWARIS PADA BALAI DIKLAT KEAGAMAAN ACEH TAHUN 2020 - Nurdin Nurdin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
The problem in learning today is that the skills of teachers in using varied media are not optimal so that the learning process seems less effective and efficient. In the learning process of Islamic Education in mawaris material, teachers are more dominant in using conventional media so that the learning outcomes of students are low. This study was intended to determine the effectiveness of the application of At-Tashil-based learning media in Islamic Islamic Studies learning material according to alumni of the High School Teacher Substantive Technical Training at the Aceh Religious Education and Training Center. This research uses a qualitative approach with a descriptive type. The data collection technique consisted of instruments, interviews, and observations. The data analysis technique was carried out in the data reduction phase, data presentation, and conclusion drawing. The results of the research findings indicate that the use of At-Tashil application-based learning media in Islamic Fiqh Mawaris learning for high school teachers seems effective in terms of use, ease, and accuracy of the results.